Analysis of Community Satisfaction in the Implementation of the Main Duties and Functions of the Head of the Environment in Lompo Riaja Village, Barru Regency. - AZ, Wahyul; Marsuki; Syahnidar , Artifah (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal